Unmet supportive care needs in adults with Li-Fraumeni syndrome: a mixed-methods study - Kiermeier, Senta; Maatouk, Imad; Nees, Juliane; Keymling, Myriam; Richter, Jenniffer; Dutzmann, Christina M.; Silchmüller, Farina; Kratz, Christian Peter; Schott, Sarah (European journal of cancer care, 2025)
Introduction: Individuals with Li-Fraumeni syndrome (LFS) face an increased risk for multiple cancers. LFS is caused by pathogenic variants in the TP53 gene and individuals with LFS are recommended intense cancer surveillance programs to improve survival. Unmet supportive care needs (uSCN) are understudied for this rare condition. This study aims to investigate uSCN to draw implications for improving healthcare for individuals with LFS in Germany. Methods: Using a mixed-methods approach, affected individuals completed the German version of the Supportive Care Needs Survey Short Form (SCNS-SF-34) and semistructured qualitative interviews. Participants were recruited through newsletters, social media, personal contact, and during routine surveillance appointments at University Hospital Heidelberg and Hannover Medical School between March 2020 and June 2021. Descriptive statistics were used to analyze the quantitative data. The interviews were audio-recorded, transcribed, and analyzed via content analysis. Results: Seventy individuals with LFS completed the survey, from which 20 have also participated in the qualitative interview. The highest number of unmet needs was indicated by the domain “psychological needs” (M = 36.90, SD = 28.91), followed by “information and health system needs” (M = 26.97, SD = 25.17). An unmet need in the domain “sexuality” was indicated by 25%-33% of participants. Interview analysis revealed four main need categories: psychological, health system and information, communication, and daily living. Conclusion: Individuals with LFS reported primarily unmet psychological and informational needs. Unmet needs may dynamically change during the different trajectories of individuals with LFS (initial diagnosis, surveillance, cancer onset, and treatment). A regular assessment and increased awareness for uSCN would be beneficial for addressing different needs at different time points.
Gesehen am 01.12.2025